Guest

Add: 5m – 7n, 3n – 4m + 2, 2m – 3mn – 5 Add: 5m – 7n, 3n – 4m + 2, 2m – 3mn – 5

Add: 
5m – 7n, 3n – 4m + 2, 2m – 3mn – 5
Add: 
5m – 7n, 3n – 4m + 2, 2m – 3mn – 5

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
one year ago
Dear Student

When term have the same algebraic factors, they are like terms. Then, we have to add the like terms
= 5m–7n + (3n–4m + 2) + (2m–3mn - 5)
= 5m–7n + 3n–4m + 2 + 2m–3mn–5
= 5m–4m + 2m–7n + 3n–3mn + 2–5
= m (5 - 4 + 2) + n (-7 + 3)–3mn + (2 - 5)
= m (3) + n (-4)–3mn + (-3)
= 3m–4n–3mn -3

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free